Implementation of Operational Competitive Rating Analysis (OCRA) Method in Determining the Best E-Commerce Application - Intan Irfanilia; Ismail Husein (Universitas Cokroaminoto Palopo, 2025)
The development of e-commerce in Indonesia is getting more and more rapid, with various platforms that offer the best services for its users. This research aims to analyze and rank the best e-commerce platforms based on several key criteria, namely transaction speed, ease of use, operational costs, security, and user service support. The method used in this study is Operational Competitiveness Rating Analysis (OCRA), which evaluates alternatives based on criteria with a linear preference approach. The results of the study show that Shopee ranks first with the highest total preference, followed by Tokopedia, Lazada, Blibli, and Bukalapak. This shows that Shopee is superior in the aspects assessed compared to other platforms. Based on these findings, it is recommended for other e-commerce platforms to improve the quality of service to increase their competitiveness. This research can also be a reference for users in choosing an e-commerce platform that suits their needs